THE BRANDING PROCESS OF UPCYCLING PRODUCT TEA TIME LABEL AS ECO-FRIENDLY PRODUCT THROUGH SOCIAL MEDIA MARKETING - Jolenta, Regina Skolastika; Setiawan, Joe Harrianto (KOMITMEN: Jurnal Ilmiah Manajemen, 2024)
Fabric waste is a major problem that has an impact on the environment, especially due to the fast fashion phenomenon. In Indonesia, small businesses have begun to emerge that use deadstock materials using upcycling techniques, one of which is Tea Time Label, which uses them to make women's hair accessories. This research wants to know more about the branding process of Tea Time Label upcycled products as a brand that loves the environment through Instagram social media. The main theory used is the branding process according to Wheeler, & Millman which consists of conducting research, clarifying strategy, designing identity, creating touchpoints, and managing assets. The research method used is descriptive qualitative. The results of this research show that the branding process of this local small and medium company is in accordance with the branding process theory mentioned above and the thing that is most often done is designing the identity and values of the Tea Time Label.